Prevalence of HIV and willingness to uptake preventive services among female sex workers in Kano State, Nigeria - Godwin Omokhagbo Emmanuel; Paul Umoh; Paul Amechi; Olaniyi Felix Sanni; Roger Abang; Ochonye Bartholomew Boniface; Ismaeel Mohammed Yahaya; Agie Muhmmad Auwal (PLoS ONE, 2025)
Background HIV remains a critical global health issue, significantly affecting key populations, particularly female sex workers who face socio-economic hardships amidst limited healthcare access and high partner turnover. This study aimed to determine the HIV prevalence and to understand FSWs’ willingness to use HIV services in Kano State, Nigeria, to inform effective intervention strategies. Method This cross-sectional survey was conducted in May 2023 among FSWs in three Local Government Areas of Kano State (Gwale, Fagge, and Tarauni), Nigeria. The participants were recruited from nightclubs and brothels across the selected communities using the snowball sampling technique. The analysis of data included descriptive statistics and logistics binary regression. Using a structured questionnaire, data were collected from 650 FSWs, all of whom were tested for HIV. Participants scoring 75% or higher on willingness to use HIV services were deemed willing. Data were analysed using Microsoft Excel and SPSS Version 28.0. Results The study involved 650 FSWs across three LGAs in Kano State, with an HIV prevalence of 8.5% and 65.8% reporting willingness to access HIV services. Willingness to take HIV Self-Testing (96.0%) and Pre-exposure Prophylaxis (66.8%) services was high, primarily driven by the desire to know and confirm HIV status (87.5%). Barriers included stigma and harassment (35.4%) and lack of free, accessible services (29.2%). FSWs in Fagge and Gwale were significantly less willing to access services compared to those in Tarauni (AOR: 0.068 and 0.180, P < 0.05). Those with a sexual debut at 18 years or above were less willing (COR: 0.569, P = 0.013), while having more than one sexual partner (COR: 1.574, P = 0.038), recent vaginal sex (AOR: 5.182, P = 0.039), and engagement in transactional sex (e.g., paid for sex, COR: 2.304, P = 0.005) were associated with higher willingness. Conclusion This study highlights the role of socio-economic challenges and stigma in shaping HIV prevalence and service uptake among female sex workers in Kano. Holistic interventions and innovative approaches are essential to address barriers, improve accessibility, and ensure sustainable outcomes.